Analisis Kepatuhan Wajib Pajak Bumi dan Bangunan Berdasarkan Realisasi Penerimaan Pajak Bumi dan Bangunan (PBB) pada Dinas Pendapatan Daerah Kabupaten Pamekasan - R Agoes Kamaroellah (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2017)
Land and Building Tax (PBB) is a Local Tax as one of the important local revenue sources to finance the implementation of the local government to establish a broad regional autonomy, real and responsible. Therefore we need taxpayer compliance in meeting the obligations it is important in the collection of taxes. Tax compliance can be seen from the revenue target and Building Tax (PBB) that have been realized. This research was conducted in the Office of Regional Revenue in Pamekasan, which in this study the authors examined the Taxpayer Compliance Analysis Based Revenues and Building Tax. The purpose of this study is to determine how large the percentage level of tax compliance Land and Building (PBB) Revenues by land and building tax (PBB). The analytical method used is descriptive method in which the data obtained from the Department of Revenue Pamekasan processed by looking at the percentage of realization of revenue from land and building tax (PBB). The author can conclude that the level of compliance in 2014 is 68.52% (Less Comply) and 2015 is 79.60% (Less Comply) and 2016 ie 81.83 % (obedient enough), so it can be said that the taxpayer on land and buildings (UN ) sufficient to adhere to their obligation to pay taxes.